Correction: Fluorido-bridged robust metal–organic frameworks for efficient C2H2/CO2 separation under moist conditions. Issue 8 (8th February 2023) - Gu, Yi-Ming; Yuan, You-You; Chen, Cailing; Zhao, Sheng-Sheng; Sun, Tian-Jun; Han, Yu; Liu, Xiao-Wei; Lai, Zhiping; Wang, Shu-Dong
Abstract : Correction for 'Fluorido-bridged robust metal–organic frameworks for efficient C2 H2 /CO2 separation under moist conditions' by Yi-Ming Gu et al., Chem. Sci., 2023, ; https://doi.org/10.1039/d2sc06699h .